Technology acquisition and smes performance, the role of innovation, export and the perception of owner-managers - Edmund Mallinguh; Christopher Wasike; Zeman Zoltan (Journal of Risk and Financial Management, 2020)
Sufficient literature supports small and medium "enterprises" (SMEs) significant role in emerging and mature economies. Still, the same research highlights varying challenges that innovative firms in developing economies face, like access to formal credit and external markets. This study examines the effect of a capital budget's proportion for acquiring new technology and sale performance between 2017-2019 using a sample of 101 Kenyan SMEs. The ordinary least square moderated mediation results indicate that: (1) the proportion of the capital budget allocated for the acquisition of technology positively and significantly influences sales; (2) the index of moderated mediation suggests that the perception of firm owner-managers towards the availability of formal credit moderates the mediated relationship between the capital budget's portion spent on technology and sales as mediated by innovation activities. However, the index is insignificant for the second mediator, export longevity. However, in the final model, both the level of innovation and export longevity positively and substantially affect sales.
Keywords: 330; perception; innovation; export; moderated-mediation; technology acquisition